Dasar Perilaku Manajemen Sumber Daya Manusia (SDM) Dalam Meningkatkan Kualitas Pendidikan : Studi di Madrasah Aliyah Tarbiyatul Mutalimin Pagaden - Siti Nur Ni'mah, Siti Nur Ni'mah; Riema Afriani Kusumadewi; Septian Eka Prahardik; Putri Anggraeni (Al-Abshar: Journal of Islamic Education Management, 2023)
This article aims to learn about Human Resource Management (HRM) in improving the quality of education in Tarbiyatul Mut’alimin Pagaden. The interview was conducted with the head of the MA Tarbiyatul Mutaailimin and the study of literature by collecting books and journals related to human resource management in improving the quality of education. The data analysis techniques in this article are narrative. Human resource management According to Handoko is the withdrawal, selection, development, maintenance, and use of human resources to both individual and organizational goals.The result of this research is that MA Tarbiyatul Muta’alimin Pagaden has already implemented human resource planning starting from recruitment, evaluation, and supervision this has become the main program because the resource as a vital tool in improving the quality and quality of education in MA Tarbiyatul mutaalimin According to the head of the school MA Targyatul Mutu’alimi Mohamad badri., M.Pd.I. and the implementation of evaluation, recruitments, development of human resources has also been carried out in MA Tarbiyatul Muta'alimin pagaden.